Correction: Effects of a low-carbohydrate diet in adults with type 1 diabetes management: A single arm non-randomised clinical trial. - Jessica L Turton; Grant D Brinkworth; Helen M Parker; David Lim; Kevin Lee; Amy Rush; Rebecca Johnson; Kieron B Rooney (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0288440.].